Atuação dos metais cobre e níquel em tecidos de Danio rerio: ênfase para análise de biomarcadores histológicos e histoquímicos da espécie Danio rerio - Novaes, Glaucia Helena Castro de Freitas (2019)
Metals are known for their toxic potential to the aquatic environment, as well as being bioaccumulative and persistent elements, which increases the concern with the concentration allowed by legislation, considering protection of biota Often, these compounds are released in the water bodies in concentrations which may not cause acute effects but may compromise the viability of biological systems in the long term, considering the continuous exposure to said elements and concentrations. In this context, liver is an important organ for the evaluation of metals toxicity due to its function of excretion and its potential to accumulate exogenous substances. In gonads metals can trigger disturbances in the production, release, transport, metabolism and action of natural hormones, which can lead to fecundity loss, males feminization and consequently imbalance to living organisms, compromising the viability of the species. Exogenous substances that act in this way are known as endocrine disrupters and their influences on individual organisms and aquatic life are not well established. One ways to identify them is through histological and histochemical analysis. Metals copper and nickel originate from natural and also artificial sources due to the generation of domestic and industrial waste, depending on the anthropic activities. They can be considered toxic or essential depending on the organism, the environment and its concentrations. In addition, they have the potential to be endocrine disruptor to aquatic organisms. In this context, the main objectives of this study were: 1) To assess copper and nickel toxicity in chronic tests through histological analysis of possible morphological alterations caused by these substances in the liver 2) to evaluate the potential as an endocrine disruptor of said metals through of gonad analysis 3) Use vitellogenin as histochemical biomarker to evaluate the presence of vitellogenin in males. In view of the above, chronic tests were carried out using the model organism Danio rerio for 21 days copper (9 μg / L) and nickel (25 μg / L) exposure in a semi-static regime, with total water exchange at every 72 hours, at a temperature of 25ºC, with feed once a day. Subsequently, the organisms were euthanized and destined to histological procedure with inclusion in paraffin, staining with Hematoxylin and Eosin (HE) for morphological analysis of gonad and liver and for analysis of vitellogenin in males were stained by the staining method for histochemical analysis proposed by Van Der Ven (2003). Changes in the liver were observed, such as nucleus hypertrophy and flattening, vacuolization, increased proportion of pycnotic nuclei and loss of cytoplasmic integrity. In male gonads, there was an increase in the proportion of spermatogonia, testicular degeneration and asynchronous development of the gonad. Through the histochemical method by staining it was possible to observe the presence of vitellogenin in males exposed to nickel, which indicates feminization of these organisms.